2019
DOI: 10.1111/jfd.12983
|View full text |Cite
|
Sign up to set email alerts
|

Development of a simple and rapid reverse transcription–loopmediated isothermal amplification (RT‐LAMP) assay for sensitive detection of tilapia lake virus

Abstract: Recently, substantial mortality of farmed and wild tilapia caused by tilapia lake virus (TiLV) infection has been observed worldwide. However, sensitive and reliable diagnostic method is limited. A reverse transcription–loopmediated isothermal amplification (RT‐LAMP) assay has been applied for the detection of TiLV nucleotide sequence. Six primers targeting two locations on the target gene based on a highly conserved sequence in the segment 1 (S1) region of the TiLV genome have been designed. The optimized RT‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 32 publications
(70 reference statements)
0
22
0
Order By: Relevance
“…The application of RT‐PCR is not particularly suitable for rapid and on‐site disease diagnosis. Therefore, two RT‐loop‐Mediated isothermal amplification (RT‐LAMP) assays based on the colorimetric changes which offer rapid, cost‐effective and easy to interpret result have been recently developed (Phusantisampan, Tattiyapong, Mutrakulcharoen, Sriariyanun, & Surachetpong, 2019; Yin et al., 2019). Both RT‐LAMP assays showed sensitivities of 80.95% and 100% for TiLV, respectively (Phusantisampan et al., 2019; Yin et al., 2019).…”
Section: Diagnosis Of Tilvmentioning
confidence: 99%
“…The application of RT‐PCR is not particularly suitable for rapid and on‐site disease diagnosis. Therefore, two RT‐loop‐Mediated isothermal amplification (RT‐LAMP) assays based on the colorimetric changes which offer rapid, cost‐effective and easy to interpret result have been recently developed (Phusantisampan, Tattiyapong, Mutrakulcharoen, Sriariyanun, & Surachetpong, 2019; Yin et al., 2019). Both RT‐LAMP assays showed sensitivities of 80.95% and 100% for TiLV, respectively (Phusantisampan et al., 2019; Yin et al., 2019).…”
Section: Diagnosis Of Tilvmentioning
confidence: 99%
“…Rapid and accurate detection of the virus is crucial for selection of TiLV-free fish broodstock in view of the vertical transmission possibilities of the virus from parents to offspring (Yamkasem et al 2019; Dong et al 2020) and to prevent disease spread through movement of live fish for aquaculture (Dong et al 2017a; Jansen et al 2018). Following the characterization of the TiLV genomes (Eyngor et al 2014; Bacharach et al 2016), several PCR methods have been published, including RT-PCR (Eyngor et al 2014), nested RT-PCR (Kembou Tsofack et al 2017), semi-nested RT-PCR (Dong et al 2017b), RT-qPCR (Kembou Tsofack et al 2017; Tattiyapong et al2018; Waiyamitra et al 2018), and RT-LAMP (Phusantisampan et al 2019; Yin et al 2019). Most of the aforementioned methods used genome segment 3 of TiLV as the target for primer design.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have confirmed that the RT-LAMP method has greater sensitivity than either standard RT-PCR or nested RT-PCR [20,22,31]. The visual assessment of the RT-LAMP assay can be independent of expensive equipment such as a PCR thermocycler or a metal thermostat-controlled heater.…”
Section: Plos Onementioning
confidence: 99%
“…Conventional detection of MNSV is performed by enzyme-linked immunosorbent assay (ELISA) or reverse transcription-polymerase chain reaction (RT-PCR) [18], but these methods have the disadvantages of taking a long time to complete, and of requiring the availability of specialized equipment and expensive consumables. Recent research has used the reverse transcription-loop-mediated isothermal amplification (RT-LAMP) to detect plant [19,20], animal [21,22] and human viruses [23,24]. This method has been shown to exhibit high sensitivity, reliability and rapid completion time; furthermore, it requires cheaper consumables and simpler equipment than the conventional RT-PCR detection method.…”
Section: Introductionmentioning
confidence: 99%